2014
DOI: 10.1111/all.12372
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis in preschool children from southern Brazil

Abstract: There are few published studies on prevalence of allergic rhinitis in preschool children. The aims of this study were to verify the prevalence, clinical characteristics, and treatment of allergic rhinitis (AR) symptoms in the first year of life adding supplementary questions to the EISL instrument. A cross-sectional study used Phase III EISL written questionnaire in addition to modified allergic rhinitis ISAAC questions. One thousand and three parents of infants answered the questionnaire: 484 (48.3%) had at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…In spite of the close connection with asthma, few studies evaluated the association between rhinitis and wheezing in preschool . In our study, children with CR had almost three times higher prevalence of CW than children without rhinitis (38.6% vs. 13.7%, respectively), and 68.4% of current wheezers reported at least one rhinitis symptom in the previous year.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In spite of the close connection with asthma, few studies evaluated the association between rhinitis and wheezing in preschool . In our study, children with CR had almost three times higher prevalence of CW than children without rhinitis (38.6% vs. 13.7%, respectively), and 68.4% of current wheezers reported at least one rhinitis symptom in the previous year.…”
Section: Discussionmentioning
confidence: 51%
“…validated ISAAC questionnaire for use in children down to 3 years old with good results; however, they focused on asthma questions. Although rhinitis questions have not gone through specific validation in this age group and questions have been raised on their specificity for rhinitis diagnosis in preschool children , it has been used in several other studies reporting rhinitis prevalence in preschoolers .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AR is rarely found in isolation. The consideration of potentially confounding symptoms and diagnoses, such as upper respiratory tract infections, and the fact that AR is frequently not diagnosed by pediatricians even though it may present in infancy, contribute to under diagnosis and under treatment [ 74 ]. In adults and children over 12 years, research has focused on the classical nasal symptoms of AR, such as nasal congestion; however, a high percentage of patients with AR also experience the ocular symptoms of allergic conjunctivitis.…”
Section: Unmet Needs and Future Research On Fexofenadine In Childrenmentioning
confidence: 99%
“…A Brazilian study used Phase III EISL and modified ISAAC questionnaires to assess rhinitis symptoms in infants aged 12–15 months. This study found that 48.3% of children had at least one episode of sneezing, runny or blocked nose without cold or flu in the first year of life, and a quarter of infants had recurrent wheezing (≥3 episodes) and wheezing was more frequent in the presence of AR symptoms . A higher prevalence in preschool children may be expected as infectious rhinitis or other types of rhinitis is common due to a wide spectrum of risk factors (e.g.…”
Section: Prevalence Burden and Comorbidities Of Armentioning
confidence: 84%